2023
DOI: 10.1182/bloodadvances.2022008562
|View full text |Cite
|
Sign up to set email alerts
|

Sézary syndrome originates from heavily mutated hematopoietic progenitors

Abstract: The pathogenesis of Cutaneous T cell lymphoma (CTCL) remains unclear. Using single-cell RNA/TCR sequencing of 32,619 CD3+CD4+, CD26+/CD7+ and 29,932 CD3+CD4+, CD26-/CD7- lymphocytes from the peripheral blood of 7 patients with CTCL, coupled to single-cell ATAC-seq of 26,411 CD3+CD4+, CD26+/CD7+ and 33,841 CD3+CD4+, CD26-/CD7- lymphocytes, we show that tumor cells in Sézary syndrome (SS) and Mycosis fungoides (MF) exhibit different phenotypes and trajectories of differentiation. When compared to MF, Sézary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The levels of csPCNA were found to vary in different CTCL cell lines, with a high expression in SS cell lines and a low expression in skin-derived MF and aggressive CTCL cell lines. This disparity could potentially be attributed to the distinct nature of SS and MF, as was recently evidenced by Harro et al, who demonstrated a distinct phenotype and differentiation trajectory for MF and SS, evidenced by their TCR repertoires and mutation profiles [67]. This difference may be attributable to differences in the nuclear-to-cytoplasmic relocalization of PCNA, as reported in neutrophils [68], or the variable expression of Annexin A2, a membrane that traffics protein to lipid rafts [61,68], as reported in other cancers [60,61].…”
Section: Discussionmentioning
confidence: 94%
“…The levels of csPCNA were found to vary in different CTCL cell lines, with a high expression in SS cell lines and a low expression in skin-derived MF and aggressive CTCL cell lines. This disparity could potentially be attributed to the distinct nature of SS and MF, as was recently evidenced by Harro et al, who demonstrated a distinct phenotype and differentiation trajectory for MF and SS, evidenced by their TCR repertoires and mutation profiles [67]. This difference may be attributable to differences in the nuclear-to-cytoplasmic relocalization of PCNA, as reported in neutrophils [68], or the variable expression of Annexin A2, a membrane that traffics protein to lipid rafts [61,68], as reported in other cancers [60,61].…”
Section: Discussionmentioning
confidence: 94%